Examining the concept of Pan-Islamism - Omer, Spahic (IIUM Press, 2021)
This article discusses the concept of pan-Islamism as one of the most important concepts of the late 19th and the early 20th centuries in Western scholarship. The article focuses on the genesis, socio-political context, and ideological purpose of the pan-Islamism thought. The conclusion made is that pan-Islamism was a Western socio-political construct intended to smear and pre-empt the prospect of a global Muslim union. It was also advocated that pan-Islamism was just another pan-ideology and pan-movement that stood in the way of the western-style modernization and democratization of the world. As such, pan-Islamism had to be impeded and neutralized by all means necessary and as much as possible. Since Sultan-Caliph Abdul Hamid II was the prime mover of pan-Islamism, his reign divided opinion like no other. Little wonder that in the West, generally, his political programs were continuously repudiated and his legacy vilified.